2022
DOI: 10.1111/liv.15244
|View full text |Cite
|
Sign up to set email alerts
|

Association between non‐alcoholic fatty liver disease and the risk of dementia: A nationwide cohort study

Abstract: Background and Aims Little is known about the association between non‐alcoholic fatty liver disease (NAFLD) and dementia. Given that hepatic steatosis is linked to abnormal fat metabolism, and fat dysregulation in the brain is related to dementia, we aimed to investigate whether NAFLD is associated with an increased risk of dementia. Methods We conducted a nationwide cohort study involving 4 031 948 subjects aged 40–69 years who underwent ≥2 health check‐ups provided by the National Health Insurance Service in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 42 publications
(98 reference statements)
4
28
0
Order By: Relevance
“…A total of four observational studies were included in the meta-analysis through systematic literature search from PubMed, Embase and Web of science until 20 April 2022. 1,[4][5][6] Pooled analysis showed that NAFLD was not linked with a higher risk of dementia on Random effect model (HR, 1.02; 95% CI, 0.91-1.14; Figure 1A), which was consistent with the results of the 'leave-one-out' sensitivity analysis (Figure 1B).…”
Section: E T T E R T O T H E E D I T O R Non-alcoholic Fatty Liver Di...supporting
confidence: 83%
See 1 more Smart Citation
“…A total of four observational studies were included in the meta-analysis through systematic literature search from PubMed, Embase and Web of science until 20 April 2022. 1,[4][5][6] Pooled analysis showed that NAFLD was not linked with a higher risk of dementia on Random effect model (HR, 1.02; 95% CI, 0.91-1.14; Figure 1A), which was consistent with the results of the 'leave-one-out' sensitivity analysis (Figure 1B).…”
Section: E T T E R T O T H E E D I T O R Non-alcoholic Fatty Liver Di...supporting
confidence: 83%
“…With great interest, we read the recent study by Kim and coworkers showing that non-alcoholic fatty liver disease (NAFLD) is associated with an increased risk of dementia in a nationwide cohort study. 1 We thank them for their significant work for clinical practice, but there exist some potential pitfalls which may affect the credibility of the results. Firstly, the baseline characteristics between NAFLD and non-NAFLD group were severely unbalanced, although multivariable analysis and propensity score matching analysis was performed to reduce confounders.…”
Section: E T T E R T O T H E E D I T O R Non-alcoholic Fatty Liver Di...mentioning
confidence: 99%
“…By contrast, a recent nationwide study found that NAFLD is associated with an increased risk of dementia [ 101 ]. The association was more pronounced among females and nonobese NAFLD subjects [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…We thank Dr. Zhou et al for their thorough review of our article. 1 We agree that the different baseline characteristics in non-alcoholic fatty liver disease (NAFLD) and non-NAFLD groups in investigating the risk of dementia deserve some attention. Yet, we are afraid that the baseline characteristics of these two groups can hardly be comparable in the real-world set.…”
Section: E T T E R T O T H E E D I T O R Non-alcoholic Fatty Liver Di...mentioning
confidence: 92%